Bourgain’s slicing problem and KLS isoperimetry up to polylog - Klartag, Bo’az; Lehec, Joseph (Geometric and functional analysis, 2022)
We prove that Bourgain’s hyperplane conjecture and the Kannan-Lovász-Simonovits (KLS) isoperimetric conjecture hold true up to a factor that is polylogarithmic in the dimension.